2019
DOI: 10.1111/vcp.12755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time and storage on toxic or pseudo‐toxic change in canine neutrophils

Abstract: | INTRODUC TI ONThe CBC is an essential component of patient health evaluations.Automated cell counters have been used since the mid-20th century 1 to rapidly obtain certain hematology data, including several red blood cell (RBC), white blood cell (WBC), and platelet (PLT) indices. However, blood smear evaluation remains a requisite part of the CBC in veterinary species, as automated analyzers do not reliably detect many clinically relevant morphologic abnormalities, such as immature granulocytes, toxic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…These discrepancies between donkeys and horses in the effect of temperature on blood parameters could be due to different viability of neutrophils, although variations amongst analyzers used in each study should also be considered ( 12 , 15 ). The pseudotoxic changes observed on blood smears kept at 24°C also has been reported in dogs ( 20 ). Lysed WBCs significantly increased (compared to basal) at 12 h in samples kept at 4 and 24°C.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…These discrepancies between donkeys and horses in the effect of temperature on blood parameters could be due to different viability of neutrophils, although variations amongst analyzers used in each study should also be considered ( 12 , 15 ). The pseudotoxic changes observed on blood smears kept at 24°C also has been reported in dogs ( 20 ). Lysed WBCs significantly increased (compared to basal) at 12 h in samples kept at 4 and 24°C.…”
Section: Discussionsupporting
confidence: 61%
“…Samples stored at 4°C showed no increase in toxic indicators for at least 48 h, which is markedly longer than reported in dogs, where pseudo-Döhle bodies and other toxic changes were apparent at 24 h ( 20 ).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Analyte stability is important given that many blood samples submitted to veterinary diagnostic laboratories are stored for at least 24 hours before analysis. Considering that neutrophils undergo morphologic changes with storage, 15 we had expected that MPXI would become unstable with storage. We found that MPXI results largely decreased with storage, resulting in significant changes in median MPXI at some time points, but results were not consistent between or within individual animals on the same instrument.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the reference intervals were not optimal for evaluating MPXI, and reference change values might be preferable, 16 however, there is no guarantee the latter would not differ between analyzers. We did not evaluate other storage temperatures, and it is possible that more consistent changes in MPXI would be seen at room temperature, based on reported morphologic changes in neutrophils 15 . We did not make blood smears to evaluate for these changes in the stored samples.…”
Section: Discussionmentioning
confidence: 99%